ANALISIS STRATEGI KOMUNIKASI DINAS SOSIAL KOTA BOGOR DALAM MENANGGULANGI ANAK JALANAN DI KOTA BOGOR - Arie Ardiwijaya; Wiranta Yudha Ginting; Layung Paramesti Martha (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
The purpose of this research is to analyze communication strategy of Bogor Social Office on establishing communication with street children in Bogor. This research used qualitative descriptive method to reveal Bogor Social Office’s situation and problem in implementing communication strategy in dealing with street children. This research took place in Bogor Social Office located in Jalan Raya Merdeka No. 142, Ciwaringin, Central Bogor, on November 2018 until April 2019. There are two subjects on this research, two key informants and two ordinary informants. Data collection technique used in this research includes depth interviews, observation, and documentation. Data validity technique was using source triangulation to compare both data collected from observation and data collected from depth interview. Source triangulation in this research is Rumah Merah Putih, one of the social foundation in Bogor. Results showes theory that been used in analyzing Strength, Weakness, Opportunity, and Threat (SWOT) are able to represent street children handling which currently done by Bogor Social Office.Keywords: communication strategy, tramp, SWOT analysis.